Penguatan Pencegahan Kekerasan Seksual Pada Anak Dan Remaja Di Dusun Kawatu Negeri Honitetu Kecamatan Inamosso Kabupaten Seram Bagian Barat - Kayus Jamlean; Anatje Joningsi Pattipeilohy (Lembaga Pengembangan Kinerja Dosen, 2022)
This community service aims to prevent sexual violence against children and teenagers in Kawatu Negeri Honitetu Hamlet, Inamosso District, West Seram Regency. The issue being faced is the high rate of sexual violence that occurs among children and teenagers in the area. The focus of this service is to provide knowledge and understanding to the community regarding the dangers of sexual violence, the importance of child protection, and preventative steps that can be taken. The method used in this research is a participatory approach through collaboration with the local community. Initial steps involve an in-depth understanding of the social and cultural situation of the village. Next, the research team interacted with local residents, community leaders, and relevant institutions to understand the challenges faced and build trust. This sexual violence prevention program includes several components. First, counseling and education is carried out through workshops, group discussions, and delivery of material to children, teenagers, parents, and educators in the village. The material presented includes identifying signs of sexual violence, how to report incidents, and self-protection efforts. The results of this community service include increasing public knowledge and awareness about sexual violence and how to prevent it. Society has become more sensitive to the signs of sexual violence in children and adolescents, and is able to take appropriate steps to protect them. In addition, the formation of a community network that cares about the issue of sexual violence helps strengthen prevention and protection efforts in Kawatu Negeri Honitetu Hamlet, Inamosso District, West Seram Regency.